Exploring Translanguaging Practices of English Teachers in Classroom Interaction - Ningrum, Sabila Puspita; Paramarta, I Made Suta; Ramendra, Dewa Putu (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study aims to explore the application of translanguaging by English teachers during learning activities. The primary focus is to identify the types of translanguaging employed by teachers, determine its frequency across different phases of learning, and examine the reasons behind its use. A descriptive qualitative method was employed, utilizing classroom observations and in-depth interviews with two English teachers as participants. The results reveal that translanguaging consistently occurred in three phases of learning: pre-activity (24 instances), core activity (65 instances), and post-activity (18 instances). Teachers primarily used translanguaging to provide instructions, explain materials, ask and answer questions, give affirmations, offer praise, and manage classroom interactions. The findings further indicate that translanguaging appeared most frequently during core activities, particularly when explaining grammar and facilitating discussions. The teachers’ reasons for using translanguaging included enhancing student comprehension, sustaining engagement, and fostering emotional connections. This study concludes that translanguaging is an effective pedagogical strategy in multilingual classrooms, as it supports students’ understanding and fosters an inclusive learning atmosphere. Nevertheless, the findings are limited by the small number of participants and the single-site context; therefore, further research with a broader scope is recommended.